PERSONAL CONFLICT IN GOHATTO: BETWEEN LIFE AND DEATH: KONFLIK PERSONAL DALAM GOHATTO: ANTARA HIDUP DAN MATI - Marisa Rianti Sutanto; Ethel Deborah Lewerissa (Jurnal Kata, 2021)
This article discusses the personal conflicts between five characters in the film Gohatto. Gohatto is a film by Japanese director, Oshima Nagisa, released in 1999. Director Oshima is one of the legendary directors in Japan who is famous for his works that elevate the uniqueness of the human personality. Likewise, with Gohatto's work, Oshima raises the fluctuation of human desires that clash with tradition and morals, and in the end meet death. The film is set in the bakumatsu era (1853-1869) and tells of the lives of swordsmen in the Shinsengumi group whose job is to protect the Tokugawa shogunate. The uniqueness of this film is that it does not exploit the heroics of samurai who express themselves under the shackles of bushido morality, but rather presents homosexuality in the lives of the swordsmen in this group. This paper will also discuss personal conflicts in five major characters, through a review of the characters’ actions based on the drive that emerge from both the conscious mind and unconscious minds. The method that will be used is psychoanalysis which refers to the theory of Sigmund Freud. The id drive which is the cause of the conflict appears dominant in the five characters and overcomes the bushido morality which is the sublime characteristic of the samurai.